The Relationship Between Principals' Leadership and Quality Culture with Learning Effectiveness in Islamic Junior High Schools - Meldi Barokah; Zulfani Sesmiarni (Journal of English Language and Education, 2026)
This study aims to examine the relationship between principals’ leadership and quality culture with learning effectiveness in State Islamic Junior High Schools (Madrasah Tsanawiyah Negeri) in East Agam Regency. A quantitative correlational design was employed. The participants consisted of 169 teachers from three madrasahs selected through total sampling. Data were collected using validated and reliable questionnaires and analyzed using descriptive statistics, Pearson correlation, and multiple linear regression. The results indicate that principals’ leadership has a strong and significant relationship with quality culture. However, both principals’ leadership and quality culture show no significant relationship, either partially or simultaneously, with learning effectiveness. These findings suggest that the influence of leadership and quality culture on learning effectiveness is indirect and contextual. Therefore, improving learning effectiveness should focus on strengthening classroom instructional practices through continuous academic supervision and enhancing teachers’ pedagogical competence.